ACUTE AND SUBCHRONIC TOXICITY OF ANACARDIUM OCCIDENTALE LINN (ANACARDIACEAE) LEAVES HEXANE EXTRACT IN MICE. - Leonard, TEDONG; Dzeufiet, Paul Désiré Djomeni; Dimo, Théophile; Asongalem, Emmanuel Acha; Sokeng, Selestin Ndogmo; Flejou, Jean-François; Callard, Patrice; Kamtchouing, Pierre (African Journal of Traditional, Complementary and Alternative Medicines, 2006)
These studies focus on the toxicity leaf hexane extract of A. occidentale L (Anacardiaceae) used in Cameroon traditional medicine for the treatment of diabetes and hypertension. Previous findings on antidiabetic and anti-inflammatory have given support to the ethnopharmacological applications of the plant. After acute oral administration, it was found that doses of the extract less than 6 g/kg are not toxic. Signs of toxicity at high doses were asthenia, anorexia, diarrhoea, and syncope. The LD50 of the extract, determined in mice of both sexes after oral administration was 16 g/kg. In the subchronic study, mice received A. occidentale at doses of 6, 10 and 14 g/kg (by oral route) for 56 days. At doses of 2, 6 and 10 g/kg of extract, repeated oral administration to mice produced a reduction in food intake, weight gain, and behavioural effects. Liver or the kidney function tests were assessed by determining serum parameters like, creatinine, transaminases, and urea. All these parameters were significantly (p<0.01) abnormal. Histopatological studies revealed evidence of microcopic lesions either in the liver or in the kidney which may be correlated with biochemical disturbances. We conclude that toxic effects of A. occidentale L hexane leaf extract occurred at higher doses than those used in Cameroon folk medicine.